Answer:
see explanation
Explanation:
12.
- 27 = 9(6 + y)
There are 2 possible approaches to solving this equation
Approach 1
divide both sides by 9
- 3 = 6 + y ( subtract 6 from both sides )
- 9 = y ⇒ y = - 9
Approach 2
distribute the parenthesis on the right side of the equation
- 27 = 54 + 9y ( subtract 54 from both sides )
- 81 = 9y ( divide both sides by 9 )
- 9 = y ⇒ y = - 9
13.
- 2(- 2x + 6) = 2 + 3x ( distribute parenthesis on left side )
4x - 12 = 2 + 3x ( subtract 3x from both sides )
x - 12 = 2 ( add 12 to both sides )
x = 14